2004
DOI: 10.1007/s11998-004-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Film formation from surfactant-free, slightly crosslinked, fluorescein-labeled polystyrene particles

Abstract: A steady state-fluorescence (SSF) technique for studying film formation from surfactant-free, slightly crosslinked polystyrene (PS) latex particles is reported. The powder films were prepared from fluorescein (F)-labeled PS particles at room temperature. The mechanically strong films were obtained by annealing these films at elevated temperatures in 5, 10, 20, and 30 min time intervals above the glass transition (T g ) temperature of polystyrene. Scattered light (I s ) and fluorescence (I F ) intensities from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…On the other hand, the increase in I P above T 0 presumably corresponds to the void closure process up to the T h point where the healing process takes place. Decrease in I P above T h can be understood by interdiffusion processes between polymer chains [45,46]. I P , I sc , and I tr curves of thick and thin PS/TiO 2 composite films for various TiO 2 layer content annealed at various temperatures are also shown in Figs.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the increase in I P above T 0 presumably corresponds to the void closure process up to the T h point where the healing process takes place. Decrease in I P above T h can be understood by interdiffusion processes between polymer chains [45,46]. I P , I sc , and I tr curves of thick and thin PS/TiO 2 composite films for various TiO 2 layer content annealed at various temperatures are also shown in Figs.…”
Section: Resultsmentioning
confidence: 95%
“…Before annealing, since the film contains many voids (i.e., the high number of polymer–air boundaries) most of the light is scattered at the air–polymer interface (surface scattering). Annealing the films first causes the closure of voids due to the viscous flow of PS polymer and then healing of the particle–particle boundaries . Therefore, I tr increases with annealing temperature as shown in Figs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…PS starts to flow due to annealing, and voids between particles can be filled due to the viscous flow. Further annealing at higher temperature causes healing and interdiffusion processes [37][38][39][40], resulting in a more transparent film.…”
Section: Scanning Electron Microscopy (Sem) Measurementsmentioning
confidence: 99%
“…It has been revealed that when annealing a hard latex system above the minimum film formation temperature (MFFT), deformation of particles first leads to void closure and then, after the voids disappear, diffusion across particleparticle boundaries starts. Hence, the quality of the hard latex films depends on the annealing time and annealing temperature [18][19][20][21][22][23][24][25][26]. However, the film formation process of a composite latex is more complicated than homogeneous latex due to the interactions between the different phases.…”
Section: Introductionmentioning
confidence: 99%